2017
DOI: 10.1021/acs.jctc.7b00274
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Reconstruction of Memory Kernels

Abstract: In recent years it has become increasingly popular to construct coarse-grained models with nonMarkovian dynamics in order to account for an incomplete separation of time scales. One challenge of a systematic coarse-graining procedure is the extraction of the dynamical properties, namely the memory kernel, from equilibrium all-atom simulations. In this paper we propose an iterative method for memory reconstruction from dynamical correlation functions. Compared to previously proposed non-iterative techniques, it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 31 publications
2
148
0
Order By: Relevance
“…Actually for liquid crystals it has recently been demonstrated that different modes of structural relaxation experience different time mappings compared to the atomistic counterpart, which is especially relevant for non‐equilibrium processes . More recently, projector–operator techniques have been devised to predict the dynamics of the coarse‐grained degrees of freedom on the basis of the underlying microscopic dynamics and, importantly, to tailor them by thermostats . An alternative Ansatz employs Markov state models to identify dynamical processes and adjust coarse‐grained models to arrive at a homogeneous time scaling …”
Section: Theory and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually for liquid crystals it has recently been demonstrated that different modes of structural relaxation experience different time mappings compared to the atomistic counterpart, which is especially relevant for non‐equilibrium processes . More recently, projector–operator techniques have been devised to predict the dynamics of the coarse‐grained degrees of freedom on the basis of the underlying microscopic dynamics and, importantly, to tailor them by thermostats . An alternative Ansatz employs Markov state models to identify dynamical processes and adjust coarse‐grained models to arrive at a homogeneous time scaling …”
Section: Theory and Simulationmentioning
confidence: 99%
“…[58,59] More recently, projector-operator techniques have been devised to predict the dynamics of the coarsegrained degrees of freedom on the basis of the underlying microscopic dynamics and, importantly, to tailor them by thermostats. [60][61][62] An alternative Ansatz employs Markov state models to identify dynamical processes and adjust coarsegrained models to arrive at a homogeneous time scaling. [63][64][65] 2.…”
Section: Recent Progress and Ongoing Developmentsmentioning
confidence: 99%
“…If required, the transport properties in the CG and AT parts of the system can be matched. This can be accomplished using local thermostats [117,118] or via the Mori-Zwanzig projection formalism [119][120][121][122][123][124] incorporating memory effects in the generalized Langevin equation. CG potentials are also density and temperature dependent [55,[125][126][127].…”
Section: Adress-single Dnamentioning
confidence: 99%
“…Bao et al 29 investigated breaking of ergodicity due to memory in non-Markovian Brownian dynamics. Recently, iterative methods have been developed to reconstruct memory kernels for generalized Langevin equations from molecular dynamics simulations by matching the force autocorrelation function or the velocity autocorrelation function between both methods 30,31 .…”
Section: Introductionmentioning
confidence: 99%